Kinematic and Dynamic Response of a Novel Engine Mechanism Design Driven by an Oscillation Arm - Călin Itu; Maria-Luminiţa Scutaru; Cătălin Iulian Pruncu; Radu Muntean (Applied Sciences, 2020)
The goal of this paper is to highlight the advantage fulfilled by a novel engine mechanism, the concept of which is based on an oscillating arm relative to the classical engine mechanism. Further, the results of this paper demonstrate the benefits of a novel type of mechanism and the major advantages in terms of functioning parameters of an engine. Their performances highly depend on the joint positions of the oscillating arm. The increases in the functional performances rate of success (i.e., piston stroke, volume of the combustion chamber or compression ratio) enable a superior engine power parameter (higher power, torque) and bring some additional improvement on the eco parameters of the engine related to consumption, emission, etc.